Pengaruh Insentif dan Etos Kerja yang Berdampak pada Kinerja Pegawai di Sekretariat Badan Penyuluhan dan Pengembangan SDM Kementerian Pertanian - Khairul Rizal (Politeknik Kelapa Sawit Citra Widya Edukasi, 2016)
The purpose of this study was to examine the effect of Incentives (X1) and the work ethic (X2) and job satisfaction (Z) on employee performance (Y). Data were collected using an instrument of the four variables. Instrument calibration is performed to test the validity and reliability coefficient. Validity calculated using product moment coefficient, and reliability was calculated using Cronbach Alpha coefficients. The model used in this study is a model of causality or influence relationships. To test the hypothesis that will be proposed in this study, the technique of analysis to be used is the analysis Strip. The study concluded that: 1) the variable incentives (X1) has a direct influence on the performance (Y) of 0.586 or 58.6% greater than the work ethic variable (X2) is -0.136, or -13.6%. Thus, that variable incentives (X1) greater influence than the variable Work Ethic (X2) to Performance; and 2) a variable incentives (X1) through job satisfaction variables have an indirect effect on performance (Y) of 0.218 or 21.8% greater than the work ethic variable (X2) is -0.085, or 08.5%. Thus, that through job satisfaction variables, variable incentives (X1) greater influence than the variable Work Ethic (X2) on employee performance (Y).